The effect of Titanium (IV) chloride surface treatment and titanium dioxide/graphenated carbon nano-tube composite photoanode to enhance charge transport and light harvesting of bifacial dye-sensitized solar cell - Lawal, Ismail; Shafie, Suhaidi; Pandey, Shyam S.; Jafaar, Haslina; Mustafa, Mohd Amrallah; Abdulmalik, Ibrahim Onuwe; Ismail, Ismayadi; Kamarudin, Mazliana Ahmad; Mohd Noor, Ikhwan Syafiq; Ahmad, Fauzan; Liu, Xinzhi (Elsevier Ltd, 2025)
This study investigates a novel photoanode architecture for bifacial dye-sensitized solar cells (B-DSSCs), integrating a graphenated carbon nano-tube (g-CNT) composite with a translucent TiCl4 (T/sp) layer and TiCl4-induced compact and blocking layers. A bilayer pristine TiO2 photoanode served as the control, while the composite variants incorporated g-CNT at 0.0025–0.0500 wt% concentrations in a cascaded structure with TiO2 (T/sp). Before TiCl4 treatment, the 0.01 wt% g-CNT variant achieved a 4.8437 % power conversion efficiency (PCE), a 42.5 % increase over the control (2.7857 %). conducting TiCl4 treatment, the 0.005 wt% g-CNT composites exhibited optimal performance with a bifacial PCE of 6.4447 %, representing a 25 % enhancement over untreated variants and a 56.8 % improvement over the control. This performance improvement trend was similarly corroborated by incident photon-to-current efficiency (IPCE) measurements. The optimized photoanode demonstrated an intermediary band gap of 3.24 eV of the three variants. FESEM imagery and EDX data confirmed g-CNT incorporation, evidenced by sp2 in-plane stretching in Raman spectra and a diffraction peak at 26.2° (002) in XRD. Electrochemical analysis revealed moderate charge collection efficiency (ηcc) in untreated samples, while the presence of g-CNT enhances charge transport. TiCl4 passivation further improved ηcc, particularly in the T/sp + TiO2/0.005 wt% g-CNT composite, achieving 44.43 % (front) and 40.63 % (back) by reducing surface trap states and recombination. These findings underscore the synergistic effect of cascade-layered TiO2, g-CNT composites, and TiCl4 treatments in enhancing light absorption and charge transport for high-performance B-DSSCs.